Transnational Politics as Cultural Circulation: Toward a Conceptual Understanding of Migrant Political Participation on the Move. (26th May 2016) - Boccagni, Paolo; Lafleur, Jean-Michel; Levitt, Peggy
Abstract: This article contributes to the burgeoning literature on transnational politics by bringing tools used by scholars of cultural diffusion and circulation into these debates. We build on research on social remittances and their potential to yield broader and deeper effects or to 'scale up' and 'scale out.' Based on a variety of empirical examples, we propose that processes such as circulation, portability, and contact, viewed through a transnational optic, help to nuance recent research on political transnationalism and its empirical indicators – including, most notably, external voting.